Pengembangan Sumber Daya Manusia (Terintegrasi Melalui Career Development, Talent Management, Succession Planning, Dan Talent Mapping 9-Box Matrix) - Ansella Yoanda; Bangun Hatoguan Simanihuruk; Hapzi Jamil; Arjun Sofianto; Heri Daman Huri Lubis; Marzuti Isra; Suhendri Suhendri; Purjianto Purjianto (Pusat Riset dan Inovasi Nasional, 2026)
Human resource (HR) development is a strategic factor in improving organizational performance and sustainability. This paper aims to examine the concepts and practices of HR development, including career development, talent management, succession planning, training and development, talent mapping using the 9-Box Matrix, workforce diversity, and affirmative action. The method used in writing this paper is a qualitative approach through a literature review, reviewing various books, scientific journals, and relevant sources. The results of the study indicate that planned career development, systematic talent management, and sound succession planning play a crucial role in ensuring the availability of competent and sustainable HR. Training and development programs tailored to organizational needs can improve employee competence and productivity. Furthermore, the implementation of talent mapping using the 9-Box Matrix helps organizations objectively identify high-potential employees, while the application of diversity principles and affirmative action encourages the creation of an inclusive and equitable work environment. Thus, integrated HR development is key to increasing organizational competitiveness and sustainability.